2010
DOI: 10.1590/s0066-782x2010005000027
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da proteína-C reativa no risco cardiovascular de adolescentes

Abstract: Artículo recibido el 31/10/08; revisado recibido el 23/08/09; aceptado el 21/10/09. ResumenFundamento: Diversos estudios sugieren que la proteína-C reactiva (PCR) se correlaciona con la enfermedad arterial coronaria en adultos. Sin embargo, esta asociación es todavía poco explorada en adolescentes.Objetivo: Evaluar la asociación entre la PCR y los factores de riesgo cardiovascular en adolescentes obesos.Métodos: Ochenta y cuatro adolescentes (12,6 ± 1,3 años), de ambos sexos, se distribuyeron en los grupos Eut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
1
3
0
2
Order By: Relevance
“…Some studies have Revista de Nutrição http://dx.doi.org/10.1590/1415-52732014000300002 indicated that excess weight is the risk factor most strongly associated with dyslipidemia and this is due to multiple metabolic causes: insulin resistance, hyperinsulinemia, hyperglycemia, increased protein transferring cholesterol esters secreted by adipocytes, among others 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have Revista de Nutrição http://dx.doi.org/10.1590/1415-52732014000300002 indicated that excess weight is the risk factor most strongly associated with dyslipidemia and this is due to multiple metabolic causes: insulin resistance, hyperinsulinemia, hyperglycemia, increased protein transferring cholesterol esters secreted by adipocytes, among others 28 .…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence in the literature of a positive correlation between elevated CRP-us levels and hyperglycemia, hypertension, smoking and presence of MS or abnormal plasma lipid levels. 6,15,[23][24][25] Hyperglycemia is related to inflammation because of formation of advanced glycation end products (AGEs), which can lead to synthesis of IL-6, to activation of macrophages and to oxidative stress, which culminates in production of CRP, contributing to inflammation. Advanced glycation end products are derived from non-enzymatic reaction of glucose (in addition to oxidation of glucose) with proteins, lipids and nucleic acids, leading to oxidative stress and subsequent development of inflammatory and thrombotic processes.…”
Section: Inflammation: Can It Be Measured?mentioning
confidence: 99%
“…Numerous studies have shown that hsCRP has a positive relationship with body mass index (BMI), overweight/obesity and body adiposity across diverse populations (Ford et al, 2001 in US children; Gildiken et al, 2007 among obese patients; Hodge et al, 2010 in Australian adults; Park et al, 2005 in Korean adults; Rexrode et al, 2003 in US women of age ≥45 years; Silva et al (2010) in Brazilian adolescents). Similarly, hsCRP has been associated with altered blood lipid profiles (Wang et al, 2011 in US overweight university students; Wu et al, 2003 in Taiwanese children) and elevated risk of coronary pathology (Pearson et al, 2003; Ridker et al, 2004).…”
Section: Introductionmentioning
confidence: 99%